The development of theory to assist the application of destination yield management - Mulvey, Michael F. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2005)
Destinations are geographical spaces where tourism experiences take place. They include the built and natural environm ent, attractions, the host community and commercial interests - predominantly SMEs. The role of destinations has changed in the past decades from a product led perspective with relatively stable markets and travel distribution channels. Intense competition, ever more demanding consumers and the eroding of traditional distribution channels by electronic intermediaries are compelling destinations and their SMEs to examine and embrace management techniques which maximise revenues and thereby increase profits. Yield management is a technique which has a successful record in large organisations, such as airlines and hotels, in maximising revenue but with limited penetration in SMEs.
Keywords: Statistics, Ph.D.; Ph.D. Trinity College Dublin